The production of the young female body in chilean advertising. The case of margarita magazine (1930-1940) - Saa Espinoza, Marcela (Última Década, 2020)
The following article provides an insight into the construction or configuration of an ideal of youth in Chile on the basis of the analysis of the representation of the young female body instilled by the Chilean magazine Margarita, in circulation from the 1930s. The analysis included the interpretation of advertising images through a semiotic reading focused on revealing their textual and visual dimension. The results of this article highlight the main ideal attributes in the young female body, which eventually became undisputed standards until today, as well as the means and strategies used by advertising for spreading, encouraging and stilling such ideal of body.